P.012 Spinal durotomy repair simulator for deliberate microsurgical practice: integration into a residency training module. (17th June 2016) - Lau, JC; Denning, L; Lownie, SP; Peters, TM; Chen, EC
Abstract : Background: Deliberate practice is one aspect of gaining competency in surgical skills. We have previously integrated a vascular microsurgery module into our residency training curriculum, and have recently described our experience with constructing patient-specific spine models for simulating lumbar spinal durotomy repair. The goal of this project is to develop the necessary infrastructure to facilitate practice on the spine model during residency. Methods: A 3D-printed plastic lumbar spine model was created from a patient computed tomography scan. L2 was manually laminectomized, and paraspinal tissues were simulated using Polyvinyl Chloride (PVC) Plastisol. Harvested bovine pericardium was sewn into tubular form as a dural substitute. The pericardial tubes were tied at either end and attached to intravenous tubing to create a closed loop water system. Results: We are developing a video tutorial describing how to setup and use the model. Residents will be recorded while performing a 1.5 cm durotomy and repair using a surgical microscope available in our training laboratory (Drake-Hunterian Neurovascular Laboratory, London, Ontario, Canada). Residents are asked to grade the realism of the model using a questionnaire. Metrics of quality are to be determined. Conclusions: Our proposed model is a cost-effective, easy-to-prepare lumbar spinal simulator that facilitates microsurgical practice during neurosurgical residency.